Implementation of The Qur'an in Modern Science Learning - Angel Mape; ardi ardi; Divi Andini; Shalmita Sakina (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2023)
Alqur'an is a very perfect human guideline, because it regulates all aspects of human life, both worldly life including very small things and the afterlife. But unfortunately, the development of the times has led to the teachings of alqur'an and further away from the monitoring and implementation of the contents of alqur'an ‟in human life. From the perspective of Islamic science, Islamic science is used as a tool to gain knowledge about Allah, pleasure and closeness to Allah. Knowledge must be able to direct a Muslim in various ways and efforts to get close to Allah SWT. The method used in this research is the literature review method by looking for various relevant theoretical references. The data sources in this study are 10 articles obtained from the database Google Scholar and Google Scholar. This study aims to find out how the Implementation of alqur'an in Modern Science Learning. Based on the results of the literature review, it can be concluded that alqur'an plays a role in the advancement of science, especially science, both in Biology, Mathematics, Physics, Chemistry, Medicine, and other sciences. In the field of biology, alqur'an explains how the creation of humans, the creation of the heavens and the earth, the functions of the structures of living things (animals), etc. In the fields of mathematics, Algebra, Sets, Geometry and Measurement, Logic, Statistics and Estimation (estimates) are several concepts mathematics in the Qur'an, and in the field of chemistry alqur'an also explains how the creation of the universe. Thus, it seems clear that learning science cannot be separated from the verses of alqur'an. Keywords : implementation,alqur'an,learning science